Personal Reflections on Tlingit Matriculture: Transcript - Ramos, Judith (Matrix, 2026)
In this recorded interview, Judith Ramos shares her personal reflections about being a Tlingit woman and Tlingit matriculture. Transcript available (see PDF).LINK TO VIDEO INTERVIEW: Personal Reflections on Tlingit Matriculture